Existência, limites e consequências da vinculação dos conselheiros de administração - Marcelo Augusto Amin Correia (2019)
This dissertation examines the existence and nature of the bond between board members andshareholders who elected them, as well as the consequences of such bond, considering the dutiesand responsibilities of the board member, and its limits in the directors behaviour. As such, theanalysis focused on the need to conciliate the still applicable Directors Guidelines for Conductwith sections 8 and 9 of article 118 of Law 6.404/76, which prescribed the self-applicableapparatus that guaranteed the effectiveness of the of the shareholders agreement. Through theinvestigation of legislation, doctrine, practice and legal precedents it was possible todemonstrate the delicate position upon which the board member is placed in the corporation.Therefore, the hypothesis, stating that the bond cannot be denied but must be reconciled withthe other applicable provisions of the law and of the companys bylaws, was confirmed. Thehope is that this study might contribute, with theoretical background, for the directors decisionto disagree or not with an eventual instruction form the shareholder.